Corrosion inhibition of carbon steel in acidic medium by orange peel extract and its main antioxidant compounds. (January 2016) - M'hiri, Nouha; Veys-Renaux, Delphine; Rocca, Emmanuel; Ioannou, Irina; Boudhrioua, Nourhéne Mihoubi; Ghoul, Mohamed
Highlights: Catechol and derived functions are responsible for flavonoids antioxidant activity. Antioxidant activity of adsorbed molecules explains cathodic inhibition. Orange peel extract inhibition is enhanced by the precipitation of a covering film. Abstract: Chemical compounds of orange peel extracts were identified and their antioxidant activities were determined. The inhibiting effect on acidic steel corrosion brought by the extract and selected antioxidant compounds (neohesperidin, naringin, ascorbic acid) was evaluated separately by electrochemical methods. Whatever the extract concentration, a significant inhibition is observed, whereas selected antioxidant compounds show only a slight effect. Both electrochemical impedance spectroscopy results and scanning electron microscopy observations after immersion reveal that the inhibiting efficiency of orange peel extract is not only due to the antioxidant activity of its compounds but also to the precipitation of a surface film.